Effect of Ball‐Milled Rice Starch and Other Functional Ingredients on Quality Attributes of Rice‐Based Dough and Noodles. (3rd February 2022) - González, Luciana Carla; Loubes, Maria Ana; Tolaba, Marcela Patricia
Abstract: Rice starch is modified by planetary ball milling. Its application as a functional ingredient in gluten‐free noodles is studied. Ten formulations based on rice flour, ball‐milled rice starch (BMRS), whole egg powder (E), and guar gum (G) are proposed to study the effect of mixture design on the technological aptitude of dough as well as on the mechanical and cooking performance of noodles. The technological quality of dough is favored by the addition of BMRS, since it confers cohesiveness. All doughs containing gum meet all the required technological attributes. The mechanical performance of cooked pasta is improved largely when guar gum and egg are incorporated into the formulation. Strength and extension values remain acceptable when the replacement of rice flour by modified starch is within 6.25–12.5%. Water absorption (WA) increase significantly (values greater than 100%) when noodles contain egg. However, the addition of egg also increase the cooking loss (CL). In contrast, guar gum allows obtaining minimum cooking loss values. The best cooking parameters are obtained with the combination of egg, gum, and modified starch (up to 12.5% of substitution), a mixture that also meet the technological and texture requirements. Abstract : Ball‐milled rice starch, egg powder (E), and guar gum (G) are evaluated as functional ingredients in gluten‐free noodles. Quality attributes of dough and noodles are studied based on 10 formulations. Ball milled rice starch confers cohesiveness to the raw dough while egg and guar gum additions enhance cooking and strength properties of pasta.